2021
DOI: 10.4103/jfmpc.jfmpc_583_21
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards COVID-19 vaccination among the public in Kerala

Abstract: Context: As COVID-19 spread across the world, vaccines were developed to fight against the spread of the new disease. Negative attitude and unwillingness to vaccinate when available may be a major hurdle in attaining effective vaccination coverage. Aims: The aim of this study was to assess the attitudes towards the COVID-19 vaccine and identify the predictors of negative attitudes towards the vaccine and identify groups most at risk of uncertainty and unwillingness to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…( 18 ) One reason that can explain this disparity is that respondents are asked about vaccination stance in the vaccination center, making it more likely that respondents have already accepted vaccination. ( 27 )…”
Section: Discussionmentioning
confidence: 99%
“…( 18 ) One reason that can explain this disparity is that respondents are asked about vaccination stance in the vaccination center, making it more likely that respondents have already accepted vaccination. ( 27 )…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, a USbased study in 2020 concluded that two-thirds of the Americans will not get the COVID-19 vaccine when it is first available, while 25% report that they do not have any intention to get vaccinated at any time [37]. In India, vaccine hesitancy was high in Tamil Nadu, more than 40% and willingness for vaccine uptake was found to be close to 90% in Kerala [38,39]. Another vaccine hesitancy survey by University College London, UK finds mistrust among 16% respondents, and 23% were confused [40].…”
Section: Negative Attitude Towards Covid-19 Vaccinementioning
confidence: 99%
“…In India, vaccine hesitancy was high in Tamil Nadu, more than 40% and willingness for vaccine uptake was found to be close to 90% in Kerala [38,39]. Another vaccine hesitancy survey by University College London, UK finds mistrust among 16% respondents, and 23% were confused [40].…”
Section: Negative Attitude Towards Covid-19 Vaccinementioning
confidence: 99%